2010
DOI: 10.13031/2013.29584
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Assessing Annual Nitrate Loads and Concentration Indicators: Part 1. Impact of Sampling Frequency and Load Estimation Algorithms

Abstract: The objectives of this study are to evaluate the uncertainty in annual nitrate loads and concentrations (such as annual average and median concentrations) as induced by infrequent sampling and by the algorithms used to compute fluxes. A total of 50 watershed-years of hourly to daily flow and concentration data gathered from nine watersheds (5 to 252 km 2) in Brittany, France, were analyzed. Original (high frequency) nitrate concentration and flow data were numerically sampled to simulate common sampling freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 31 publications
2
76
1
Order By: Relevance
“…For both P forms monitored in drainage waters, no such differences were found. During the REs, a dilution of N-NO 3 in drainage waters usually prevailed, whilst for both P-PO 4 and P tot , the concentrations usually rose with elevated discharge, which is in accordance with many monitoring campaigns in tile-drained catchments [5,12,18,25,31]. The only exceptions were sites PD1 and PD2, with Cfw N-NO 3 higher in ESs than in RSs.…”
Section: Dynamics Of N and P Concentrationssupporting
confidence: 86%
See 4 more Smart Citations
“…For both P forms monitored in drainage waters, no such differences were found. During the REs, a dilution of N-NO 3 in drainage waters usually prevailed, whilst for both P-PO 4 and P tot , the concentrations usually rose with elevated discharge, which is in accordance with many monitoring campaigns in tile-drained catchments [5,12,18,25,31]. The only exceptions were sites PD1 and PD2, with Cfw N-NO 3 higher in ESs than in RSs.…”
Section: Dynamics Of N and P Concentrationssupporting
confidence: 86%
“…For nitrate-N load estimation, two methods have been recommended by numerous authors: (1) linear interpolation, a period weighted method, and (2) flow-weighted mean concentration, an averaging method [18,24,25]. Previous research has shown that the uncertainty due to infrequent sampling and nutrient load estimation approaches for drainage systems or small streams is often much greater than the uncertainty brought about by other steps in the sample collection process [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations